Consensus Management of Gastrointestinal Events Associated with Delayed-Release Dimethyl Fumarate: A Delphi Study. Issue 2 (December 2015) - Theodore Phillips, J.; Erwin, April; Agrella, Stephanie; Kremenchutzky, Marcelo; Kramer, John; Darkes, Malcolm; Kendter, Jonathan; Abourjaily, Heather; Rana, Jitesh; Fox, Robert
Abstract Introduction Delayed-release dimethyl fumarate (DMF, also known as gastro-resistant DMF) is indicated for the treatment of patients with relapsing multiple sclerosis. Gastrointestinal (GI) adverse events (AEs) occur with DMF therapy. Methods We used a Delphi process to reach consensus among North American clinicians on effective real-world management strategies for GI AEs associated with DMF. Clinicians were asked to complete two rounds of questionnaires developed by a steering committee; consensus in round 2 was attained if ≥70% of respondents agreed on a particular strategy. Results Consensus was reached on several strategies to manage GI AEs, including administering DMF with food, slow titration, dose reduction, and use of symptomatic therapies. Conclusion These consensus strategies provide clinicians with information on real-world approaches used to address the tolerability of DMF in patients with multiple sclerosis. Funding Biogen.